Antonomasias Formed on the Basis of the Names of Mythological, Religious-Legendary Heroes - Yokub Saidov; Risolat Achilova (Researchparks Publishing, 2022)
The article deals with the phenomenon of antonomasia in language and speech, its essence and lexical-semantic features and the issues such as the role of antonomasies formed on the basis of the names of mythological, religious-legendary heroes. There are three groups of antonomases according to their semantic features, namely a) antonomases formed on the basis of popular historical events; b) antonomases based on myths; c) literary works - it is recommended to study the antonomas formed on the basis of the images in them.